Dialect Grapholects at the Beginning of the 21st Century as a Manifestation of the Vitality and Continuity of Dialectal Codes - Aliūkaitė, Daiva; Meiliūnaitė, Violeta (Verbum, 2022)
The paper presents a case study on written dialectality. The material used for the research is the Eastern Aukštaitian (EA) texts published in the almanacs titled “A Waking Spring” (“Bundanti versmė”) (2013, 2014). The paper develops an approach for “reading” written dialectality, provides theoretical insights about the concept of a dialect grapholect, presents a dialectological analysis of the EA texts, assessing the vitality of the distinctive features, and also includes commentary on the non-standard spelling choices applied to reflect these features through the grapholect. In the given paper written dialectality is considered to be an indication of the vitality and continuity of dialectal codes because, unlike in oral dialectality, the informants-authors put effort into demonstrating dialect. The distinctive features of the EA and of its subdialects represented in the grapholects suggest the idea of their vitality in apparent time. The orthographic choices of the informants-authors are considered as dialect respelling. The EA grapholect is found to be fluctuating, while the orthographic choices for conveying the features of the subdialects are somewhat more stable, however, still in a stage of development as well. Therefore, it is more accurate to discuss the grapholects (plural), rather than a grapholect (singular) of the EA or the subdialect.